The Influence of PSAK 71 Implementation on Firm Value with Investor Confidence as a Moderating Variable - Arief Harjanto; Nella Yantiana; Muhammad Fahmi; Syarif M Helmi; Nina F Dosinta (Poltanesa, 2025)
This study aims to analyze the influence of the implementation of the Indonesian Financial Accounting Standards Statement (PSAK) 71 on firm value, with investor confidence as a moderating variable. The research focuses on banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A quantitative approach with a causal-comparative research design was employed. The data were analyzed using SPSS version 25.The results indicate that the Allowance for Impairment Losses (CKPN), as a representation of PSAK 71 implementation, has a significant effect on firm value. This is evidenced by a significance value of 0.000 and a t-statistic of -17.685, which exceeds the critical t-value, thereby supporting the first hypothesis. However, investor confidence does not moderate the relationship between CKPN and firm value, as demonstrated by a t-statistic of -0.435, which is below the critical t-value, and a significance level above 0.05. These findings suggest that although CKPN influences market perceptions of risk and corporate valuation, investor confidence is not yet strong enough to mitigate this effect. This study contributes to the understanding of the dynamics surrounding the application of PSAK 71 and market perceptions of financial stability in the banking sector.